Theory and history of folklore - Propp, V. I͡A. (Vladimir I͡Akovlevich) 1895-1970; Martin, Ariadna; Martin, Richard; Liberman, Anatoly (Minneapolis, MN University of Minnesota Press, 1984)
"This book will give Propp's admirers in the English-speaking world a whole new perspective on this distinguished scholar's contribution to folkloristics. Liberman provides the necessary background in terms of Russian/Soviet intellectual (and political) currents to place Propp's work in a new light. No student of structuralism in folklore can afford to miss Liberman's anthology."--Alan Dundes (from cover)
The nature of folklore -- folklore and reality -- The principles of classifying folklore genres -- On the historicity of folklore -- The structural and historical study of the wondertale -- Transformations of the wondertale -- Historical roots of the wondertale: premises -- Historical roots of the wondertale: the wondertale as a whole -- Ritual laughter in folklore -- Russian heroic epic poetry: introduction.
Photocopy.
Includes bibliography references (pages 213-232) and indexes.
In English. Original language: Russian.
Keywords: Folk literature, Eastern Slavic -- History and criticism; Tales -- Soviet Union -- History and criticism; Tales -- History and criticism; Folklore -- Methodology